Advance garbage monitoring system / Muhammad Khairi Daniel Muhamad Halmee - Muhamad Halmee, Muhammad Khairi Daniel (2024)
The Advanced Garbage Monitoring System is a real-time solution for monitoring garbage bin levels to tackle waste management issues. It uses ultrasonic and infrared sensors as inputs, with the Arduino UNO microcontroller to process and interpret data. User-friendly outputs like an LCD display, LEDs, and a buzzer communicate the trash condition to users. The LCD offers a friendly interface, and LEDs change colors to indicate different trash levels. The buzzer alerts both management and users when the garbage reaches a critical level. Before implementing the system, detailed hardware simulation in Proteus helped identify and solve potential issues. Despite challenges with coding and hardware compatibility, the project succeeded through the guidance of the project supervisor, thorough research, and ongoing testing. The Advanced Garbage Monitoring System proves to be a practical and effective solution for enhancing waste management and promoting a cleaner environment